PENGARUH PROFITABILITAS, LIKUIDITAS, HUTANG DAN UKURAN PERUSAHAAN TERHADAP DIVIDEND PAYOUT RATIO - Regina Fricilya D. Yasmin; Gendro Wiyono; Ratih Kusumawardhani (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
The aim of this paper was to examined the influence of profitability, cash flow, liquidity, leverage and firm size towards dividend payout ratio. The sample includes 11 manufactur companis in consumer goods industry sector listed in Inodnesia Stock Exchange (IDX) on the year period 2016-2019. We use time series regression (panel data) to test the hypothesis of this study. The results shows that independent variables of profitability, liquidity, and leverage have positive and significant impact in dividend payout ratio; whereas, the independent variables of cash flow and firm size have negative and significant impact on dividend payout ratio.Kata Kunci : Dividend Payout Ratio, Profitabilitas, Likuiditas, Hutang, Ukuran Perusahaan